Effect of Wollastonite Filler on the Experimental and Microstructural Analysis of Epoxy Composite Reinforced with E-glass Fibre - Lokesh, K. S.; Pinto, Thomas; Shrinivasa Mayya, D.; Shanmugam, Bharath Kumar; Panduranga, B. P.; Hanumanthappa, Harish; Mohanraj, G. T. (Journal of the Institution of Engineers (India): Series D, 2022)
In the present study, the polymer composite was produced with epoxy, E-glass and wollastonite as the matrix, reinforcement and filler material, respectively. The present study investigates the effect of the filler material on the mechanical performance of developed composite specimens. The reinforcement material selected was woven and chopped-type fibre material. The filler material composition in the woven and chopped-type specimens was individually varied with 0%, 1%, 3%, 5% and 7%. The specimen was subject to mechanical testing, viz., tensile and flexural strength tests. Further, the wear rate of the normal specimen was tested to 5, 10 and 15 min. Additionally, the specimen was subjected to SEM (scanning electron microscope) analysis after attaining fracture for each study. The results showed that the specimen with 1% filler material had better tensile strength. It was also found that the flexural strength was good and was increasing with the filler material. The wear rate was reduced with the increase in filler material composition in the specimen. The results show that the woven fabric specimen shows better mechanical performance than the chopped specimen.